Pemanfaatan Kulit Buah Carica sebagai Bahan Baku Pembuatan Eco-Enzyme di Desa Dieng Kulon - Aditia, Edit Lesa; Nurofaza Sakila; Hafidhah Nur Fathonah; Azizi, Refiona Putri; Ramadhani, Rasya Aulia; Iskandar, Aubrey Nadira Zahra; Aziz, Farisi Abdul; Nugraha, Raindra Ravi Malik (Jurnal Pusat Inovasi Masyarakat, 2024)
Carica is a typical highland fruit that is one of the mainstay commodities of the Dieng Plateau. This plant is widely produced as processed syrup which will be marketed as a typical souvenir of Dieng Kulon Village. This program aims to strengthen the capacity of the Dieng Syariah Women Farmers Group (KWT) of Dieng Kulon Village in maximizing the utilization of carica fruit. This activity involved 24 KWT members who produce an average of 25 kilograms of carica peel waste per day. The implementation method begins with exploring and identifying problems, program planning, implementation, and monitoring. The manufacture of eco-enzyme began with the collection of 9 kilograms of carica peel from the members of KWT Dieng Syariah then mixed with water and brown sugar then stirred and gallons were closed. The fermentation process was carried out for 90 days. Monitoring of the eco-enzyme was done on the 3rd, 7th, 30th, and 90th day. This program produced 3 gallons of eco-enzyme which is still in the fermentation process. However, the last observation process at 30 days of fermentation, the eco-enzyme product was dark brown in color, fresh sour aroma, with a high amount of gas. This shows the tendency of success of the eco-enzyme product made.